The Influence of Product Quality, Brand Image, and Packaging on Customer Loyalty of Dove Products in Surabaya City, Indonesia - Alamsah, Hafid Akmal; Purwanto, Sugeng (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to analyze the influence of product quality, brand image, and packaging on customer loyalty to Dove products in Surabaya. The research method used is quantitative with a descriptive approach. Data were collected through the distribution of questionnaires to 105 respondents who had used Dove products. The data analysis technique employed is Partial Least Squares (PLS). The results show that the three independent variables, product quality, brand image, and packaging, simultaneously positively and significantly affect customer loyalty. These findings indicate that to maintain consumer loyalty, Dove needs to consistently ensure product quality, strengthen brand image, and continuously innovate in packaging design and functionality. This research offers strategic recommendations for companies to enhance personal care product market competitiveness.